Characterization of B1+ field variation in brain at 3 T using 385 healthy individuals across the lifespan. Issue 2 (21st September 2021) - MacLennan, Thomas; Seres, Peter; Rickard, Julia; Stolz, Emily; Beaulieu, Christian; Wilman, Alan H.
Abstract: Purpose: The transmit field B 1 + at 3 T in brain affects the spatial uniformity and contrast of most image acquisitions. Here, B 1 + spatial variation in brain at 3 T is characterized in a large healthy population. Methods: Bloch‐Siegert B 1 + maps were acquired at 3 T from 385 healthy subjects aged 5–90 years on a single MRI system. After transforming all B 1 + maps to a standard brain atlas space, region‐of‐interest analysis was performed, and intersubject voxel‐wise coefficient of variation was calculated across the whole brain. The B 1 + variability due to age and brain size was studied separately in males and females, along with B 1 + variability due to nonideal transmit calibration. Results: The voxel‐based mean coefficient of variation was 4.0% across all subjects, and the difference in B 1 + between central (left thalamus) and outer regions (left frontal gray matter) was 24.2% ± 2.3%. The least intersubject variability occurred in central regions, whereas regions toward brain edges increased markedly in variation. The B 1 + variability with age was mostly attributed to lifespan changes in CSF volume (which alters brain conductivity) and head orientation. Larger brain size correlated with more B 1 + inhomogeneity ( p  < .001). Varying head position and anatomy resulted in an inaccurate transmit calibration. Conclusion: In standard atlas space, intersubject B 1 + variability at 3 T was relatively small in a large population aged 5–90 years. The B 1 + varied with age‐related changes of CSF volume and head orientation, as well as differences in brain size and transmit calibration.